Market power and risk taking behavior of banks - Dam, Kaniska; Zendejas Castillo, Susana Wendy (Estudios Económicos de El Colegio de México, 2006)
We consider a monopolistically competitive banking sector in order to analyze the effects of market concentration on the risk-taking behavior of banks. We show that, under full deposit insurance, a higher level of competition induces banks to invest on a risky asset. When the market concentration is high, banks tend to take less risk. We also show that maximum social welfare is achieved either through free entry or through entry restriction.